The Majestic [videorecording (DVD)] - Darabont, Frank; Carrey, Jim, 1962-; Balaban, Bob; Briscoe, Brent; DeMunn, Jeffrey, 1947-; Garfield, Allen, 1939-2020-; Holbrook, Hal; Holden, Laurie; Landau, Martin, 1928-2017; Rifkin, Ron; Stiers, David Ogden; Whitmore, James, 1921-2009 ([Warner Home Video], 2002)
Peter Appleton, a 1950s Hollywood screenwriter who is about to see his first screenplay made into a film, is mistakenly called before the House Un-American Activities Committee. As a result, the studio pulls the plans for the film. Peter then finds himself in a small California town after a car accident takes his memory. There, the townspeople believe he is local hero Luke Trimble. Peter settles into his life at the Majestic theater, as Luke Trimble, until his memory begins to resurface and govenrment men track him down.